2011
DOI: 10.1108/00070701111097376
|View full text |Cite
|
Sign up to set email alerts
|

Differences between younger and older populations in nutrition label reading habits

Abstract: PurposeThe purpose of this paper is to identify the socio‐demographic and health variables of a representative sample of Croatian subjects over 15 years of age associated with reading nutrition labels and, in particular, to examine the association of age characteristics of “label users” with nutrition reading habits.Design/methodology/approachA total of 1,011 randomly selected subjects over 15 years of age were interviewed by telephone. Moreover, 638 “label users” were recruited for assessing nutrition label h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
(27 reference statements)
3
26
1
1
Order By: Relevance
“…In an earlier study Meiden and Edris (1990) as cited by Siu and Tsoi (1998p.25) revealed that the use of nutrition information by UK consumers is notably low. Similarly, Ranilovic and Baric (2011), reported in their study of Croatian consumers that 36 percent of the subjects had never read nutrition labels during the last 12 months whilst 24.8 percent claimed they rarely read nutrition labels. In Malawi Kasapila and Shawa (2011) found that only 29.1 percent used the information.…”
Section: Nutritional Information Usementioning
confidence: 93%
See 4 more Smart Citations
“…In an earlier study Meiden and Edris (1990) as cited by Siu and Tsoi (1998p.25) revealed that the use of nutrition information by UK consumers is notably low. Similarly, Ranilovic and Baric (2011), reported in their study of Croatian consumers that 36 percent of the subjects had never read nutrition labels during the last 12 months whilst 24.8 percent claimed they rarely read nutrition labels. In Malawi Kasapila and Shawa (2011) found that only 29.1 percent used the information.…”
Section: Nutritional Information Usementioning
confidence: 93%
“…According to them, income and educational level disparities between urban and rural consumers accounted for the observed usage differences. Ranilovic and Baric (2011) found that in Croatia females, the highest educated participants, those still undergoing education, the physically active, and those on a special diet were more likely to use nutrition information when purchasing food. Mannell et al (2006) found that French consumers who are most likely to use nutritional information are those on special diet (p=.0004), women (p=.0000), and those older than 40 years old (p=.0151).…”
Section: Determinants Of Nutritional Information Usementioning
confidence: 97%
See 3 more Smart Citations